Itinerário terapêutico de pessoas com hanseníase e deficiência adquirida: a análise do diagnóstico tardio - Hespanhol, Mirella Chaves Laragnoit [UNIFESP] (2019)
Leprosy is a transmissible, neglected and incapacitating disease. In Brazil, 25,218 new cases of leprosy were diagnosed in 2016. The endemic disease continues to be the subject of studies, since it is observed a reduction in the prevalence of the illness, but with continuous registration of new cases per year and heterogeneous distribution throughout the country. In the diagnosis, expressive percentages of grade II disability assessment observed, that is, people who have acquired deficiencies due to the disease. In the state of São Paulo in the year 2016, 14.1% of the new cases presented grade II, as an epidemiological indicator that evidences the late diagnosis. This study aimed to analyze the therapeutic itinerary of the person with leprosy and acquired deficiency identified in the diagnosis. This is a qualitative study of the exploratory and descriptive type. The data produced obtained through epidemiological survey, documental analysis and in-depth interviews with people with leprosy; the material was submitted to content analysis, thematic category. The scenario chosen were two municipalities in the metropolitan region of BaixadaSantista: Praia Grande and São Vicente. The municipalities showed similarities in the Constitution of health services, with similar epidemiological profiles and in the year 2016, the occurrence of grade II was identified in 15.38% of the patients evaluated in Praia Grande and in 16.66% in São Vicente. All eligible participants were interviewed, totaling 4 people, 3 men and one woman, age between 45 and 61 years, 3 were retired due to disability and 1 continued to exercise the work. The participants presented distinct care trajectories to achieve healthcare. The categories weredivided in four themes: health care; Body in leprosy; Incapacities in leprosy and late diagnosis. Through the analysis of the intricate therapeutic itineraries, concluding that the factors that contributed to the late diagnosis were: the neglect in attention the health needs, observed by the difficulty of the participants in accessing the diagnosis and timely treatment of leprosy. The historical intertwining between "leper" and leprosy that perpetuates the stigma; Absence of information on the signs and symptoms of leprosy among the population. The inability of the professionals for the diagnosis that contributed to the invalidation of the complaints of the sick people and demonstrated the fragility of care. The study revealed the role of the participants who, through the lay act, in search of care, models the health system, thus demonstrating the real plasticity of health resources. It revealed to the reference service its responsibility, with new challenges and confrontations in the possible advances in health education for the awareness and information for the diagnosis of leprosy. Also emphasized the study of the therapeutic itinerary as a powerful tool for the analysis of health care.